DAMPAK KONSERVASI MANUSKRIP TERHADAP MINAT TULIS KADER MUHAMMADIYAH (Studi Kasus Muhammadiyah Corner Perpustakaan UMY) - Muhamad Jubaidi (UPT. Perpustakaan Universitas Muhammadiyah Ponorogo, 2020)
For more than a century Muhammadiyah was founded, exactly 106 years ago this organization was born in Yogyakarta. Various manuscripts are currently managed at the Muhammadiyah Corner of the Muhamadiyah University Library in Yogyakarta (UMY), as a preliminary step for the maintenance of digitizing manuscript conservation in an effort to preserve and maintain the authenticity of the manuscript. Conservation is carried out in the Muhammadiyah Corner room so visitors to the Muhammadiyah Corner can watch the process carried out by the librarian at each stage. The purpose of this study was to determine the extent of the impact of the manuscript conservation process on Muhammadiyah Corner on the written interest of Muhammadiyah cadres who witnessed the conservation process. While the research method uses qualitative methods. The informants used were three people with data processing techniques through observation, interviews, and documentation. From the research that has been carried out, it can be produced that manuscript conservation activities have an impact on the interest of Muhammadiyah cadres to write various kinds of works.Keywords: Conservation, Manuscript, Writing Interest